1995
DOI: 10.1177/0145482x9508900110
|View full text |Cite
|
Sign up to set email alerts
|

Housing Design and Persons with Visual Impairment: Report of Focus-Group Discussions

Abstract: This article describes the impact of positive and negative housing-design features on the everyday functioning of persons who are blind and visually impaired in their homes based on information obtained in focus-group discussions with consumers, parents, and professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
3
9
0
1
Order By: Relevance
“…Similar to previous research on the housing design features of people who are visually impaired (Long, 1995), our research found that the four participants had functional needs that were similar to those of the participants who were visually impaired in Long's study. From the interviews in our study, however, it was evident that the participants' primary design concerns in their shared living space were based not only on tactile features, but on visual factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Similar to previous research on the housing design features of people who are visually impaired (Long, 1995), our research found that the four participants had functional needs that were similar to those of the participants who were visually impaired in Long's study. From the interviews in our study, however, it was evident that the participants' primary design concerns in their shared living space were based not only on tactile features, but on visual factors.…”
Section: Discussionsupporting
confidence: 86%
“…The spatial orientation approach, used in areas such as orientation and mobility training, provides a series of systematic strategies and skills to help individuals who are visually impaired adapt to preexisting structures and layouts (Hill & Rieser, 1993). Studies on housing design attempt to establish a system for individuals who are sighted to design internal layouts for individuals who are visually impaired, thus improving the mobility and independence of people with visual impairments at home (Long, 1995). Neither of these two orientations, however, extends to how individuals who are visually impaired design their own living areas.…”
Section: Practice Reportmentioning
confidence: 99%
“…Bright artificial light was also recommended by Marquardt (2011), Lawrence et al (2009) and Kelly, Innes and Dincarslan (2011), with Van Hoof et al (2010) amongst others suggesting that this could promote better nutrition, prevent falls and modify behavioural issues. Similarly, for people with sight loss, the literature recommended bright light, preferably daylight (Lawrence and Murray 2009; Littlefair 2010; Long 1995; Utton 2009), with Torrington and Lewis (2011) highlighting the need to control glare from daylight. For people with sight loss, good lighting could improve safety (La Grow et al 2006), but also quality of life (Brunnström et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…For people with sight loss, good lighting could improve safety (La Grow et al 2006), but also quality of life (Brunnström et al 2004). The literature on sight loss noted that people's preferences may vary (Littlefair 2010; Long 1995), and research participants spoke of their need for controllable light (Long 1995; Unwin et al 2009). Where literature focused on people with both dementia and sight loss, the need to maximise natural light was again emphasised (Goodman and Watson 2010; Homes and Communities Agency 2009), whilst avoiding excessive contrast or glare.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the provision of a minimal standard of physical design features in the home and public buildings is now mandatory, the design of the outdoor urban environment is subject to local authority discretion and, unfortunately, local planning officers tend to be reluctant to impose too many disabled access requirements (Imrie and Hall, 2001). Long (1995) has argued that this has a disproportionate impact on children with visual impairments because:…”
Section: Disabled People's Access To the Urban Environmentmentioning
confidence: 99%